COMPANY SIZE IN RESPONSE TO EARNINGS MANAGEMENT AND COMPANY PERFORMANCE - Eni Wuryani (Universitas Hayam Wuruk Perbanas, 2012)
Company size has been assumed to be an influential factor in any businesses. Therefore, anycompany might be also induced by this factor when dealing with its performance. This researchaimed to analyze the effect of firm size on earnings management and corporate performance.This study was done by means of census with the population of 69 go public companies.They have been the participants of Corporate Governance Perception Index (CGPI)period 2004-2008. The variable of company size was measured by using the logarithm ofassets while that of earnings management using discretionary accruals. In measuring firmperformance variable, the study uses Tobins Q. The results of this study show a significantnegative effect of firm size on earnings management. Large-sized companies will avoid doingearnings management. Beside, the size of company has a significant and positive effect oncompany performance. Large-sized companies will have a chance to get a greater opportunityto profit through the sale of shares.